Spectroscopy of V341 Arae: A Nearby Nova-like Variable Inside a Bow Shock Nebula *Based in part on observations with the 1.5 m telescope operated by the SMARTS Consortium at Cerro Tololo Interamerican Observatory. Based in part on observations collected at the European Organisation for Astronomical Research in the southern hemisphere under ESO programme 073.D-0157(A). (12th July 2018) - Bond, Howard E.; Miszalski, Brent
Abstract: V341 Arae is a 10th-magnitude variable star in the southern hemisphere, discovered over a century ago by Henrietta Leavitt, but relatively little studied since then. Although historically considered to be a Cepheid, it is actually blue and coincides with an X-ray source. The star lies near the edge of the large, faint H α nebula Fr 2–11, discovered by D. Frew, who showed that V341 Ara is actually a cataclysmic variable (CV). His deep imaging of the nebula revealed a bow-shock morphology in the immediate vicinity of the star. We have carried out spectroscopic monitoring of V341 Ara, and we confirm that it is a nova-like CV, with an orbital period of 0.15216 days (3.652 hr). We show that V341 Ara is remarkably similar to the previously known BZ Cam, a nova-like CV with a nearly identical orbital period, associated with the bow shock nebula EGB 4. Archival sky-survey photometry shows that V341 Ara normally varies between V ≃ 10.5 and 11, with a characteristic timescale ranging from about 10 to 16 days. V341 Ara lies well off-center within Fr 2–11. We speculate that either the star is undergoing a chance high-speed encounter with a small interstellar cloud, or that the nebula was ejected from the star itself in a nova outburst in the fairly distant past. At a distance of only 156 pc, V341 Ara is one of the nearest and brightest known nova-like variables, and we encourage further studies.